Effects of Different Types of Fillers on Dry Wear Characteristics of Carbon-Epoxy Composite - Mahmood, Ibtihal A.; Soud, Wafa A.; Abdullah, Orhan S. (Al-Khwarizmi Engineering Journal, 2013)
Experimental investigations had been done in this research to demonstrate the effect of carbon fiber and Ceramic fillers contents on the tribological behaviour of (15% volume fraction) carbon-epoxy composite system under varying volume fraction, load, time and sliding distance. The wear resistance were investigated according to ASTM G99-05standard using pin on disc machine to present the composite tribological behaviour. The influence of three ceramic fillers, granite, perlite and calcium carbonate (CaCO3), on the wear of the carbon fabric reinforced epoxy composites under dry sliding conditions has been investigated. The effect of variants in volume fraction, applied load, time and sliding distance on the wear behaviour of polymer composites is studied by measuring the weight changes . In the experiments with wear test pin having flat face in contact with hardening rotating steel disc, sliding speed, time and loads in the range of 200 RPM, 300–900s and 40–60 N respectively was used. It is observed that the wear resistance increase with the increasing of reinforcement material volume fraction while, the wear rate increases with increasing of applied load, time and sliding distance. The results showed that the filler of granite perlite and CaCO3 as filler materials in carbon epoxy composites will increase the wear resistance of the composite greatly than carbon fiber fillers epoxy composite only and granite filled CE Composite exhibited the maximum wear resistance.